The legality of Botswana's import bans under the SACU agreement of 2002: an analysis of the SACU agreement's trade liberalization framework - Mhapha, Thabo (Department of Commercial Law, 2025)
The Southern African Customs Union (SACU) is the world's oldest functioning customs union, founded in 1910. A key objective of SACU, evident through its 2002 Agreement (the Agreement), is to facilitate the cross-border movement of goods between the territories of the respective member countries, or in other words, trade liberalisation. SACU's trade liberalisation objectives are in line with Article XXIV of the General Agreement on Tariffs and Trade (GATT). Article XXIV of the GATT provides the legal framework for customs unions under international trade law. The overarching objective of the multilateral trading system is to achieve freer trade. However, in recent years, the Government of Botswana has introduced and implemented a series of import bans mainly on agricultural products from SACU member states. These bans have been reasoned on Botswana's need to attain self-sufficiency and reduce its import bill. Even more recently, Botswana has announced an extension of its import bans on fresh produce, which includes tomatoes, potatoes, onions and other produce and has doubled the number of restricted items to 32. This extension has been met with wide criticism from neighbouring South Africa, which is Botswana's largest import partner. South African farmers have raised serious concerns about the bans, asserting that the bans constitute a violation of the Agreement. These claims have found support within the South African government which has indicated its intention to initiate talks on the issue. This research examines these developments to establish whether these bans contradict Botswana's trade liberalisation requirements as stipulated by the Agreement. The study delineates the legal framework for trade liberalisation under the Agreement to determine whether these bans are legal under the Agreement and determine the extent to which SACU member countries may limit trade amongst themselves. Additionally, as customs unions exist within the broader framework of the GATT, the research then analyses whether the extent of trade liberalisation provided for under the Agreement is consistent with Articles XI and XXIV of GATT.